PENGARUH GRATIS ONGKOS KIRIM, KEPERCAYAAN, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE - Khasanah, Rohmawati Nur; Ruswaji, Ruswaji; Susanti, Ike; Sustyorini, Emalia Nova (Universitas Nusa Cendana, 2024)
This research aims to determine the effect of free shipping, trust, and online customer reviews on purchasing decisions on e-commerce Shopee in Tambakrigadung Village. This type of research is quantitative research. The population in this study are customers who online shopping through Shopee in Tambakrigadung Village. The sampling technique used a purposive sampling method using the Slovin formula to obtain a sample size of 100 respondents. The data collection technique uses online questionnaire distribution via Google Form which has been tested for validity and reliability. The data analysis technique used classical assumption tests, multiple linear regression, coefficient of determination, t-test, and f-test using SPSS 26. The results of this research state that the free shipping, trust, and online customer review variables partially and simultaneously influence purchasing decisions on e-commerce Shopee in Tambakrigadung Village. The trust variable is the most dominant variable among other variables on purchasing decisions. Keywords: Free Shipping; Trust; Online Customer Review; Purchasing Decisions